Musculoskeletal health conditions among older populations in urban slums in sub-Saharan Africa. Issue 2 (April 2017) - Aboderin, Isabella; Nanyonjo, Agnes
Abstract: Background: Debate on the burden of musculoskeletal (MSK) conditions in lower and middle income countries is intensifying; yet, little knowledge so far exists on patterns and impacts of such conditions among general or older adult populations in sub-Saharan Africa (SSA). The objectives of this study are to examine the prevalence, potential predictors, and sequelae of MSK among older adults residing in two low resource informal urban settlements or "slums" in Nairobi Kenya. Methods: Data on older adults aged 60 years and over from two unrelated cross-sectional surveys on the older slum populations are used: a 2006/7 survey on the social, health, and overall well-being of older people (sample N = 831), and a 2016 survey on realities and impacts of long-term care and social protection for older adults (sample n = 1026). Uni and multivariate regressions on the 2006/7 data are employed to examine relationships of back pain and symptoms of arthritis with sex, age, wealth, unemployment, diagnoses of hypertension, and diabetes; and with indicators of subjective well-being and functional ability. Descriptive frequencies and chi-squared tests of association are used on 2016 data to identify the overall prevalence and locations of activity limiting MSK pain, and sex differences in these. Results: Prevalence of past month back pain and past 2 week symptoms of arthritis was 44% and 42.6%, respectively. Respective prevalence of past month activity limiting back pain and joint pain was 13.9% and 22.7%. A total of 42.6% of slum residents with a current health problem report MSK as the most severe problem. In multivariate regressions, female sex, unemployment, and diagnosis of hypertension are predictive of back pain and symptoms of arthritis. Both conditions are associated with raised odds of having lower quality of life, poorer life satisfaction, and depressive symptoms, and with mobility impairments and self-care difficulties. Conclusions: MSK conditions are salient, and a likely key cause of impaired subjective well-being and functioning among older slum populations in SSA. Further research on determinants and consequences of such conditions in older slum populations is required to inform debate on responses to MSK as part of efforts to reorient SSA health systems to aging and to improve slum health.